Charge storage and electron transport properties of gold nanoparticles decorating a urethane-methacrylate comb polymer network - Patil, Sumati; Datar, Suwarna; Rekha, N.; Asha, S. K.; Dharmadhikari, C. V. (Nanoscale, 2013)
We propose enhanced charge storage capacity of nanoparticles based polymer films. A flat band voltage window varying from 5-7 V is obtained leading to a trapped charge density of the order of 10(13) cm(-2). These results vary for two distinct morphologies obtained due to decoration of a urethane-methacrylate comb polymer (UMCP) network by gold nanoparticles (AuNPs). Films have been further investigated for morphology, optical, charge storage, and electron transport properties using techniques like scanning electron microscopy (SEM), atomic force microscopy (AFM), absorption spectroscopy (UV-Vis), scanning tunneling microscopy/spectroscopy (STM/STS) and capacitance versus voltage (C-V) measurements. SEM and AFM confirm either the deposition of AuNPs inside the UMCP network or the formation of ring like structures depending on the deposition sequence. STS measurements performed on both films are compared with bare UMCP and AuNPs films. Current versus voltage (I-V) characteristics so obtained are discussed in the light of electron transport mechanisms in such materials.